Postnatal Catch-Up Growth After Suspected Fetal Growth Restriction at Term - van Wyk, Linda; Boers, Kim E.; van Wassenaer-Leemhuis, Aleid G.; van der Post, Joris A. M.; Bremer, Henk A.; Delemarre, Friso M. C.; Gordijn, Sanne J.; Bloemenkamp, Kitty W. M.; Roumen, Frans J. M. E.; Porath, Martina; van Lith, Jan M. M.; Mol, Ben W. J.; et al. (Frontiers in Endocrinology, 2019)
Objective: The aim of this study was to study growth patterns of children born after suspected fetal growth restriction (FGR) at term and to compare the effect of induction of labor (IoL) and expectant management (EM), also in relation to neurodevelopmental and behavioral outcome at age 2. Methods: We performed a 2 years' follow-up of growth of children included in the Disproportionate Intrauterine Growth Restriction Trial at Term (DIGITAT) study, a Randomized Controlled Trial (RCT) comparing IoL with EM in pregnancies with suspected FGR at term. We collected data on child growth until the age of 2 years. Standard deviation scores (SDSs) for height and weight were calculated at different ages. We assessed the effects of IoL compared with EM and the effects of a birth weight below or above the 3rd or 10th centile on catch-up growth. Target height SDSs were calculated using the height of both parents. Results: We found a significant increase in SDS in the first 2 years. Children born after EM showed more catch-up growth in the first month [height: mean difference −0.7 (95% CI: 0.2; 1.3)] and weight [mean difference −0.5 (95% CI: 0.3; 0.7)]. Children born with a birth weight below the 3rd and 10th centiles showed more catch-up growth after 1 year [mean difference −0.8 SDS (95% CI: −1.1; −0.5)] and after 2 years [mean difference −0.7 SDS (95% CI: −1.2; −0.2)] as compared to children with a birth weight above the 3rd and 10th centiles. SDS at birth had the strongest effect on adverse neurodevelopmental outcome at 2 years of age. Conclusion: After FGR at term, postnatal catch-up growth is generally present and associated with the degree of FGR. Obstetric management in FGR influences postnatal growth. Longer-term follow-up is therefore needed and should be directed at growth and physical health. Clinical Trial Registration:www.ClinicalTrials.gov, identifier SRCTN10363217.